The Influence of Case Method and Spiritual Intelligence on Critical Thinking Skills of Faculty of Economics and Business, Padang State University Education Students - Reza Nur Wahid; Marwan Marwan (Universitas Negeri Semarang, 2025)
This study aims to examine the differences in students' critical thinking skills between those taught using the Socratic-based Case Method and the non-Socratic Case Method, as well as to analyze the interaction between the Case Method and spiritual intelligence on critical thinking skills. A quasi-experimental design with a pre-test and post-test non-equivalent control group design was employed. The participants were students from the Economics Education Study Program, Faculty of Economics and Business, Universitas Negeri Padang, enrolled in the Introduction to Microeconomics course during the 2024/2025 academic year. The findings reveal significant differences in critical thinking skills between students taught with the Socratic-based and non-Socratic Case Methods. Additionally, differences were observed based on students' levels of spiritual intelligence, and an interaction effect was identified between the learning model and spiritual intelligence on students' critical thinking skills.